2022
DOI: 10.3390/ijerph19148242
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Anemia and Falls among Postmenopausal Women in Korea

Abstract: This study was conducted to explore the relationship between anemia and falls in postmenopausal women. The relationships between energy, protein, iron, and vitamin C intake were also checked. The data of this study are a combination of data from the Korea National Health and Nutrition Examination Survey (KNHANES) collected from the KNHANES VI-2,3 (2014–2015) and VII-1,2,3 (2016–2018). Falls and anemia were compared according to the subjects’ characteristics. Phi and Cramer’s V coefficient were applied to find … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Similar studies state that there is no relationship between nutrient intake and the incidence of anemia [64]. Other research states that pregnant women who are sufficient to meet their iron intake also experience anemia [65]. In contrast to research where the majority of pregnant women did not adhere to taking Fe tablets (<60 tablets) had an impact on the incidence of anemia (p<0.05) [62].…”
Section: Discussionmentioning
confidence: 99%
“…Similar studies state that there is no relationship between nutrient intake and the incidence of anemia [64]. Other research states that pregnant women who are sufficient to meet their iron intake also experience anemia [65]. In contrast to research where the majority of pregnant women did not adhere to taking Fe tablets (<60 tablets) had an impact on the incidence of anemia (p<0.05) [62].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a curved relationship was observed in the overweight subgroup. Currently, dietary iron intake is mainly focused on pregnancy and anemia among women (25,26). However, it has been shown that dietary iron intake exhibited no relationship with non-pregnancy diseases such as gynecological cancers (15).…”
Section: Discussionmentioning
confidence: 99%
“…For example, men may benefit from assessments related to the ability to climb stairs while women benefit from nutritional assessments. Nutrition and its relationship to falls have been established previously 4. There has been a large body of literature exploring the efficacy of exercise interventions in preventing falls, a Cochrane review found that multicomponent exercise programmes, tai chi and others were effective interventions in community-dwelling older adults 5.…”
Section: Commentarymentioning
confidence: 99%